Level of Online Learning Motivation in Ners Professional Students in Online Learning at University Muhammadiyah Malang - Ririn Harini; Juwitasari Juwitasari (STIKes Patria Husada Blitar, 2021)
Background: Since the covid-19 pandemic occurred at the end of 2019, the education process which is usually carried out face-to-face must be done through online learning. Due to this pandemic condition, it is still difficult for Nurse Profession level students to adapt. This study was determined the level of learning motivation during online learning at the University of Muhammadiyah Malang. Method: This descriptive analytical study was analyzed by a IBM SPSS 26 version for windows. The number of respondents as many as 78 students of ners 22 class and ners 23 class was recruited by total sampling from October 2020 - January 18, 2021. The level of motivation data was identified by the Watsin questionnaire using whatsapp, zoom and google meet online platforms. Results: The 19 respondents or about 25% of participants was less than and equal to 19 years old, 22 peoples or about 28% of student nurses aged 20 years, 19 peoples or about 24% of nursing students aged 21 years, and the remaining 18 peoples or about 23% of student aged 22 years and over. The descriptive analysis showed that the average level of motivation of Nurse students during online learning was 63,14. Conclusion: the level of motivation of Nursing students during online learning in hospitals during the COVID-19 pandemic was categorized in sufficient level. The further strengthens was the needs of variety online learning model towards nursing professional level during pandemic of COVID 19.